A comparative study of optimum risk portfolio and eigen portfolio on the Indian stock market. (3rd January 2022) - Sen, Jaydip; Mehtab, Sidra
Designing an optimum portfolio that allocates weights to its constituent stocks in a way that achieves the best trade-off between the return and the risk is a challenging research problem. This paper presents three approaches to portfolio design, viz, the minimum risk portfolio, the optimum risk portfolio, and the eigen portfolio, for seven important sectors of the Indian stock market. The daily historical prices of the stocks are scraped from Yahoo Finance website from January 1, 2016, to December 31, 2020. Three portfolios are built for each of the seven sectors chosen for this study, and the portfolios are analysed on the training data based on several metrics such as annualised return and risk, weights assigned to the constituent stocks, the correlation heatmaps, and the principal components of the eigen portfolios. Finally, the optimum risk portfolios and the eigen portfolios for all sectors are tested on their return over a period of a six-month period.